Efektivitas Teknik Cinema Therapy untuk Menurunkan Academic burnout pada Mahasiswa Fakultas Psikologi Universitas Negeri Makassar - Wardhani, Rieska Cendra Ayu; Murdiana, Sitti; Ismail, Ismalandari (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Students who are faced with the academic pressures of lectures and exceed the limits of their abilities tend to experience academic burnout as a result of difficulties in dealing with these pressures efficiently. Students experiencing academic burnout will show an attitude of exhaustion characterized by feeling psychologically and physically tired, an attitude of cynicism of indifference or distancing themselves from lecture activities, and an attitude of professional efficacy with decreased self-confidence so that they tend to be passive. The aim of this research is to determine the effectiveness of cinema therapy techniques in reducing academic burnout in students at the psychology faculty of Makassar State University. The participants in this research were 12 students, divided into two groups, namely experimental and control. The criteria for participants in this research are (i) active students at the Faculty of Psychology, Makassar State University, aged 19-25 years and experiencing high or medium academic burnout. The sampling technique uses purposive sampling. This research uses Mann Whitney and Wilcoxon test analysis techniques with the results of the hypothesis H0 being rejected and Ha being accepted, so the cinema therapy technique is effective in reducing academic burnout in Makassar State University students. The implications of this research illustrate that the application of cinema therapy techniques can help significantly reduce the academic burnout experienced by students.